Key pedagogical principles and their major obstacles as perceived by comprehensive school teachers - Atjonen, Päivi; Korkeakoski, Esko; Mehtäläinen, Jouko (Teachers and teaching, theory and practice, 2011)
The general pedagogical knowledge of teachers is not often investigated in comparison to content knowledge and pedagogical content knowledge. In this article, a more comprehensive outlook on teachers' skills and knowledge without regard to subject-specific nuances is discussed in relation to classroom management strategies, the organization of pupils' learning, and effective communication techniques and teaching. The aim of this research was to describe what comprehensive school teachers believe to be the main pedagogical principles and what their perceived obstacles seem to be. These principles and their obstacles were examined according to gender, school level, class size, and school subject. A random sample of all Finnish schools was obtained based on the probability proportional to size (PPS)-sample method. In the second phase of sampling, teachers were selected from the schools, so that they represented primary and secondary levels of comprehensive school. The data was gathered by the questionnaire returned by 362 class teachers (primary level/grade four, response rate 85%) and 1989 subject teachers (secondary level/grades seven to nine, response rate 61%). Descriptions for three open-ended questions were analyzed both quantitatively and qualitatively, following a category system which was both data-based and theory-based. The means of 10 structured Likert-scale items were calculated and compared (t-test, one-way ANOVA). The key pedagogical principles focused on teaching-learning arrangements and methods, relationship to pupils and learning environment, general educational principles, and expected skills and attitudes. The first two were among the most often described cases of successful teaching-learning events. Obstacles toward the implementation of personally important principles into pedagogical practice were related to the learning requirements, to the pupils and groups of pupils, and to the teachers' and pupils' backgrounds. The results properly reflected various theoretical conceptualizations of pedagogical principles and indicated the teachers' rich understanding of good practice. The results increase our understanding of teachers' pedagogical decision-making, which can be used in both initial and in-service teacher education.